Argentine literature in English: publishing translations subsidized by PROSUR (2010–2020) - Szpilbarg, Daniela (2024)
This article focuses on national institutes´ translation policies and draws on works that have recast the notion of soft power for the study of cultural production. Our goal is to analyze how Argentine literature circulates abroad, specifically through translations into hypercentral English, with subsidies from the Programa Sur de Traducciones (South Translation Program, or PROSUR). We trace the history of PROSUR – run by the Argentine Ministry of Foreign Affairs, International Trade, and Worship – and analyze statistical data from institutional databases. Likewise, we study the catalogues, collections, websites, and paratexts of the books sold by a group of publishing houses that have received PROSUR subsidies. Our article suggests that, regardless of the various traits of the titles and the specific profiles of each publishing house, we may identify common trends in relation to how the presses exercise soft power, produce meaning, and introduce Argentine literature in three main ways that we define as political resistance, Latin American literature, and women´s writing. Thus, this article is a contribution to the notion of soft power by shifting the focus away from the intent around cultural policy and toward frequently overlooked considerations around the practices of the recipients of cultural policies.